Revision of Longitarsus cyanipennis species group, with description of eleven new species (Coleoptera: Chrysomelidae: Galerucinae: Alticitae) - Liang, Zu-Long; Konstantinov, Alexander S.; Ruan, Yong-Ying; Yang, Xing-Ke; Ge, Si-Qin (Zootaxa, 2026)
Fifteen species belonging to the Longitarsus cyanipennis species group are revised. All species are described or redescribed, accompanied by images of external morphology and genitalia. A key to the species of the group is provided. Eleven new species are described: L. bryanti Liang & Konstantinov sp. nov., L. jinpingensis Liang & Konstantinov sp. nov., L. lijiangensis Liang & Konstantinov sp. nov., L. lodayi Liang & Konstantinov sp. nov., L. mauliki Liang & Konstantinov sp. nov., L. latipenis Liang & Konstantinov sp. nov., L. medogensis Liang & Konstantinov sp. nov., L. radialis Liang & Konstantinov sp. nov., L. viridis Liang & Konstantinov sp. nov., L. volkovitshi Liang & Konstantinov sp. nov., and L. zhejiangensis Liang & Konstantinov sp. nov. Longitarsus warchalowskii Scherer, 1969 is resurrected from synonymy with L. indigonaceus Lopatin, 1963, while L. indigonaceus Lopatin, 1963 syn. nov. is proposed as a junior synonym of L. cyanipennis Bryant, 1924. Amongst the species group, four species are recorded in Mêdog County, i.e., L. warchalowskii, L. bryanti sp. nov., L. latipenis sp. nov., and L. medogensis sp. nov.